1986
DOI: 10.1002/ctpp.19860260105
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Scattering of Electrons by a Cut‐Off Coulomb Potential at Low Energies

Abstract: Elastic scattering of electrons by cut-off Coulomb potential U,(r) is investigated, whereU,(r) = 0, for r > r, and U,(r) = -l/r + l/rc for r S r,. This is first considered in terms of classical, and later quantum mechanical (partial wave) methods in the low energy range 0 5 E 5 l/rc, where E is the energy of the free electron. Scattering in this energy region displays a number of particular characteristics, such as back scattering, at certain energies. It can be concluded that some agreement does exist between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…I n the previous paper [3] we showed that in transport cross sections obtained there was a good agreement between the classical and quantum mechanical results, for E 2 e2/2r,. Here we consider the case when the nonideality parameter F, = e2/kBTrc, is I', < 1, so that the wnge, where we have E < e2/rc, is of no importance.…”
Section: (4)supporting
confidence: 67%
See 1 more Smart Citation
“…I n the previous paper [3] we showed that in transport cross sections obtained there was a good agreement between the classical and quantum mechanical results, for E 2 e2/2r,. Here we consider the case when the nonideality parameter F, = e2/kBTrc, is I', < 1, so that the wnge, where we have E < e2/rc, is of no importance.…”
Section: (4)supporting
confidence: 67%
“…Here we take veff similar to [5]: (3) where ni and n, are the ionic or atomic concentrations, respectively. a,i and a,, are the momentnm transfer cross sections for the electron scattering on screened ions and atoms, while l / y is the well knownspitzer factor which is used to take into account the electronelectron interaction.…”
Section: Basic Equationsmentioning
confidence: 99%
“…There is a possibility that the use of the modified potential (8) should give even better results. The usage of the Coulomb cut-off potential, see [3][4][5][6][7] for example, has led to a good agreement for the transport coefficients of plasma. However the optical properties of those dense plasma are not covered in such manner.…”
Section: Discussionmentioning
confidence: 86%
“…In Mihajlov et al (2015) the significance of the model potential used in this paper was emphasized. One of the model Coulomb screening potentials, known as the cut-off potential, had already been introduced in Suchy (1964), and had been investigated in connection with the transport plasma properties in Mihajlov et al (1986). This potential is given by…”
Section: The Potential and Electrostatic Screening Modelmentioning
confidence: 99%